Prohibiting Tear Gas for Riot Control with the Chemical Weapons Convention: Reaching Beyond the Battlefield? - Nivia Nivia (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
Chemical Weapons Convention 1993 prohibits tear gas as a method of warfare but permits its use as a law enforcement tool, particularly for domestic riot control. Such normative provision results in massive violations of human rights towards civilians caused by the use of tear gas in several states. This research analyses tear gas historically and compares its similar characteristic with chemical weapons in general to see whether tear gas shall be banned in all contexts like others chemical weapons. Through normative research and qualitative analysis, this research shows that there is no fundamental difference between tear gas and chemical weapon. It cannot be separated from its characteristic which is also indiscriminate and caused unnecessary suffering, even against non-rioter. That being said, international law shall treat those instruments equally in a way that totally bans both of them